Barriers of faculty development in under graduate medical education of Bangladesh (Bangladesh Journal of Medical Education, 2018)
This descriptive cross sectional study was carried out to identify the existing barriers of faculty development in undergraduate medical education of Bangladesh. This study was conducted in eight (four Government and four Non- Government) medical colleges in Bangladesh over a period from July 2015 to June 2016. A semi-structured self-administered questionnaire was used for collecting data from individual teacher. Total 103 teachers responded to the questionnaire. Regarding barriers of faculty development about 47% respondents opined that insufficient initiatives by the institute, 38% of teachers opined too much workload. About 24% teachers opined lack of recognition and reward, 19% opined about lack of fund, 14% teachers' opined lack of organized programme, 12% about lack of qualified resource person for faculty development programme. From the findings of present study it is evident that medical institutes of Bangladesh should play a bit more active role for faculty development programme, should organize arrangement for adequate resources particularly faculty development instructors and funding for faculty development.Bangladesh Journal of Medical Education Vol.9(1) 2018: 10-13